2022
DOI: 10.1080/22221751.2022.2125346
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and clinical features of hand, foot and mouth disease requiring hospitalization after the use of enterovirus A71 inactivated vaccine in chengdu, China, 2017-2022: a descriptive study

Abstract: Three inactivated enterovirus A71 (EV-A71) vaccines have been widely vaccinated among children in the targeted age group in mainland China since mid-2016. However, comprehensive virological surveillance of hand, foot and mouth disease (HFMD) over multiple years after the use of EV-A71 vaccines has rarely been conducted. Using long-term data extracted from the Public Health and Clinical Center of Chengdu, we described the clinical, aetiological, and epidemiological characteristics of HFMD inpatients after the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Subsequently, the number of HFMD cases rose sharply in 2018, followed by a continuous decline until 2022. These trends are consistent with those reported in other studies [ 13 , 15 , 16 ]. It is noteworthy that the number of HFMD cases remained low from 2020 to 2022, particularly from February to June 2020 and from September to December 2022, mainly due to the strict control measures against COVID-19, which has reduced the chances of children coming into contact with infected or potentially infected children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Subsequently, the number of HFMD cases rose sharply in 2018, followed by a continuous decline until 2022. These trends are consistent with those reported in other studies [ 13 , 15 , 16 ]. It is noteworthy that the number of HFMD cases remained low from 2020 to 2022, particularly from February to June 2020 and from September to December 2022, mainly due to the strict control measures against COVID-19, which has reduced the chances of children coming into contact with infected or potentially infected children.…”
Section: Discussionsupporting
confidence: 93%
“…The diagnosis of HFMD was established based on current epidemiology, clinical manifestation and virological investigation in accordance with the Chinese guidelines for the diagnosis and treatment of HFMD (2018 edition) [ 13 ]. In this study, we included all suspected and combined cases of HFMD, including those diagnosed with herpetic angina and other highly suspected or laboratory-confirmed EV infections, due to the overlapping clinical symptoms and similar etiology to HFMD.…”
Section: Methodsmentioning
confidence: 99%
“…Our investigation showed that CVA6 was the dominant serotype of HFMD in Hubei Province, followed by CVA16. Previous studies have reported that CVA6 has gradually replaced EV-A71 and CVA16 as the predominant serotypes [ 18 , 19 ]. The prevalence of HFMD varies seasonally, and different enterovirus serotypes are prevalent in different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that CVA16 was more susceptible to NPIs than CVA6. All cases in Shanghai in 2020 were diagnosed as CVA6 [ 20 ] and CVA16 circulating was at a very low epidemic level in many cities in China in 2020 and 2021 [ 19 , 21 ]. CVA6 transmission throughout the year had little effect on NPIs except for the closure of all schools, nurseries, and infant institutions in the first half of 2020.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In recent years, the outbreak of RSV infection in China, Europe and the United States has brought serious burden to society. 3–5 Currently, there are approved RSV monoclonal antibodies designed for infants and children up to 2 years of age, 6 as well as two vaccines developed for older adults. 7 These advancements signify significant strides in RSV management.…”
Section: Introductionmentioning
confidence: 99%